The Impact of Female Sex Hormones on Competitiveness - Thomas Buser (Tinbergen Institute, 2009)
We use fluctuations of female sex hormones occurring naturally over the menstrual cycle or induced by hormonal contraceptives to determine the importance of sex hormones in explaining gender differences in competitiveness. Participants in a laboratory experiment solve a simple arithmetics task first under a piece rate and then under a competitive tournament scheme. Subjects can then choose which compensation scheme to apply in a third round. We find that sex hormones have a strong effect on whether women select into the competitive environment. The observed patterns are consistent with a negative impact especially of progesterone on competitiveness and our results therefore provide a partial biological explanation for gender differences in competitiveness. We consider three possible indirect pathways through which sex hormones could affect competitiveness: via an impact on risk aversion, via an impact on performance, and via an impact on overconfidence. None of these hold up to the data and we conclude that sex hormones have a more direct impact on competitiveness.
Keywords: C91; C92; J16; 330; competitiveness; gender differences; hormones; lab experiment